Industrialization, urbanization, and land use in China - Zhang, Xiaobo; Mount, Timothy D.; Boisvert, Richard N. (International Food Policy Research Institute, 2000)
Rapid industrial development and urbanization transfer more and more land away from agricultural production, threatening China’s capability to feed itself. This paper analyzes the determinants of land use by modeling arable land and sown area separately. An inverse U-shaped relationship between land use intensity and industrialization is explored both theoretically and empirically. The findings highlight the conflict between the two policy goals of industrialization and grain self-sufficiency in the end. Several policy recommendations are offered to reconcile the conflict.